Auto Feeder Pakan Ikan berbasis IoT dan Panel Surya untuk Kolam Ikan di Desa Jubung Kecamatan Sukorambi Kabupaten Jember - Catur Suko Sarwono; Khairul Anam; Gramandha Wega Intyanto; Andrita Ceriana Eska; Didik Suharijadi (Politeknik Negeri Jember, 2026)
Local economic development for freshwater fish farming has significantly improved the community's economy. In Jubung Village, Sukorambi District, Jember Regency, there are eight freshwater ponds with a total area of 1,639 m2 managed by several community groups. These ponds are well managed and cultivated, but have not yet utilized auto-feeder fish feed technology and solar panels. As a field analysis, it was discovered that the determining factors for the success of fish farming are the number of stockings and the frequency of manual feeding. Based on this, a community service activity was carried out by presenting Appropriate Technology (TTG) to improve the management of freshwater fish ponds, using an auto-feeder fish feed device integrated with an IoT platform, and solar panels. This community service was carried out by applying the device to fish ponds in Jubung Village. Next, socialization activities were carried out to pond managers to utilize the technology. As a result of the community service activity, among others, an understanding of the technology for freshwater fish farming using an auto-feeder fish device that is carried out automatically or accessed remotely, as well as the use of solar panels to operate the device without using electricity.